Pengaruh Karakter Eksekutif, Kompensasi Eksekutif, dan Intensitas Modal Terhadap Penghindaran Pajak - Siti Mustafidah; Hari Stiawan (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2022)
The purpose of this study was to examine and obtain empirical evidence regarding the effect of Executive Character, Executive Compensation, and Capital Intensity on Tax Avoidance. In this study, tax avoidance is measured using the company's Cash Effective Tax Rates (CETR), namely the amount of tax payments divided by profit before tax. This study uses a sample of companies listed on the IDX on the Kompas 100 index for the years 2017-2021.The method of determining the sample of this research is by using purposive sampling method and also using Econometric Views (Eviews 9) version 8.0.0.0 to analyze the data. The type of research in this study is quantitative, data obtained from 7 companies that were used as research samples for (5) years, so that the total observations used were 35 companies with audited financial statements. The analysis technique used is multiple linear regression. The results of this study state that: The results of the partial test (t test) show that (1) Executive Character has no effect on Tax Avoidance, (2) Executive Compensation has a significant negative effect on Tax Avoidance, (3) Capital Intensity has no effect on Tax Avoidance , (4) that Executive Character, Executive Compensation, and Capital Intensity simultaneously have a significant effect on Tax Avoidance in companies listed on Kompas 100 in 2017-2021